Educated consumers don't believe artificial meat is the solution to the problems with the meat industry - Aurélie Hocquette; Carla Lambert; Clémentine Sinquin; Laure Peterolff; Zoé Wagner; Sarah P F Bonny; André Lebert; Jean-François Hocquette (Journal of Integrative Agriculture, 2015)
The production of in vitro meat by cell culture has been suggested by some scientists as one solution to address the major challenges facing our society. Firstly, consumers would like the meat industry to reduce potential discomfort of animals on modern farms, or even to avoid killing animals to eat them. Secondly, citizens would like meat producers to reduce potential environmental deterioration by livestock and finally, there is a need to reduce world hunger by increasing protein resources while the global population is predicted to grow rapidly. According to its promoters, artificial meat has a potential to make eating animals unnecessary, to reduce carbon footprint of meat production and to satisfy all the nutritional needs and desires of consumers and citizens. To check these assumptions, a total of 817 educated people (mainly scientists and students) were interviewed worldwide by internet in addition to 865 French educated people. We also interviewed 208 persons (mainly scientists) after an oral presentation regarding artificial meat. Results of the three surveys were similar, but differed between males and females. More than half of the respondents believed that “artificial meat” was feasible and realistic. However, there was no majority to think that artificial meat will be healthy and tasty, except respondents who were in favour of artificial meat. A large majority of the respondents believed that the meat industry is facing important problems related to the protection of the environment, animal welfare or inefficient meat production to feed humanity. However, respondents did not believe that artificial meat will be the solution to solve the mentioned problems with the meat industry, especially respondents who were against artificial meat. The vast majority of consumers wished to continue to eat meat even they would accept to consume less meat in a context of increasing food needs. Only a minority of respondents (from 5 to 11%) would recommend or accept to eat in vitro meat instead of meat produced from farm animals. Despite these limitations, 38 to 47% of the respondents would continue to support research on artificial meat, but a majority of them believed that artificial meat will not be accepted by consumers in the future, except for respondents who were in favour of artificial meat. We speculated that the apparent contradictory answers to this survey expressed the fact that people trust scientists who are supposed to continuously discover new technologies potentially useful in a long term future for the human beings, but people also expressed concern for their health and were not convinced that artificial meat will be tasty, safe and healthy enough to be accepted by consumers.